Multitext Learning: Efforts to Improve Literacy Students in Indonesia - Darmiyanti, Astuti; Taufik, Muhammad (Indonesian Journal of Librarianship, 2021)
Problem Statement: Development of literacy lists reading as the main literacy skill in the 21st century. Although society in general especially students are no longer illiterate, reading interest and reading literacy skills in Indonesia, based on PISA, OCED, and UNESCO, are still relatively low in terms of multi text study. For this reason, multi text-based learning is needed for improving the students’ literacy. Purpose: This study aims to describe how multi-text learning is taught to students to increase their interest in reading and literacy. Method: This research uses a qualitative research with literature study method. Data sources of this research are reference books and scientific journal articles that have relevance to the research. Results: Multi-literacy learning or also known as multiliteracy is one of the learning designs used in the context of 2013 curriculum. This concept is designed to meet the skills needed in the 21st century. Multiliteracy learning is created to connect 4 multiliteracy skills (reading, writing, spoken language, and, using IT). The stages of multi-text literacy learning cycle are as follows: 1) involving: 2) responding; 3) elaborating; 4) reviewing; 5) presenting. Conclusion: Multitext learning is still barely taught to students in Indonesia. Only 30% of students have multitext reading knowledge and skills. In fact, multitext learning can be used as an alternative solution to increase reading ability and interest. Multi-text learning needs to be supported by teacher's skills namely creating interesting and adequate multitext materials and ensuring decent reading sources according to its age of reader, as well as for parents, they have to be able to advise their children to choose multitext as the reading sources. Keywords: Literacy; Multitext Learning; Reading